Theoretical-Methodological Elements for Comparative Analysis of Social Inequalities in Life Courses - Muñiz Terra, Leticia Magalí (2020)
Social inequalities are one of the structural problem areas of Western capitalist societies, and are of particular relevance both in Europe and in Latin America. Sociological studies on the issue account for the complexity of the phenomenon by presenting their constitution and consolidation based on the analysis of institutional and subjective aspects, which include the particularities, on the one hand, of the socio-economic systems of countries and regions; and, on the other hand, the representations, dispositions and actions deployed by individuals in order to deal with and live in an unequal world.